2010
DOI: 10.1111/j.1524-4725.2010.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month, Double-Blind, Randomized, Split-Face Study to Compare the Efficacy and Safety of Calcium Hydroxylapatite (CaHA) Mixed with Lidocaine and CaHA Alone for Correction of Nasolabial Fold Wrinkles

Abstract: BACKGROUND Safety, pain, duration of effect, and patient satisfaction are important concerns for physicians performing dermal filler injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The Food and Drug Administration has since approved the option of combining lidocaine with RDF. One of the articles in this supplement compares premixed lidocaine and RDF with RDF alone for treatment of nasolabial folds 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Food and Drug Administration has since approved the option of combining lidocaine with RDF. One of the articles in this supplement compares premixed lidocaine and RDF with RDF alone for treatment of nasolabial folds 2 …”
mentioning
confidence: 99%
“…One of the articles in this supplement compares premixed lidocaine and RDF with RDF alone for treatment of nasolabial folds. 2 Other physicians have described their experiences in pretreating with lidocaine followed by injection of RDF. [3][4][5] For this randomized and evaluator-blinded study, investigators addressed the safety and efficacy of RDF itself for rejuvenation of the aging hand, using only a small volume of lidocaine administered before injection.…”
mentioning
confidence: 99%
“…Pain on administration of CaHA is significantly reduced by mixing CaHA with 0.2–0.4 mL of 2% lidocaine, administered with 1.3 mL syringes. Furthermore, the viscosity and extrusion force to inject the product is also significantly decreased with this dilution (20,21).…”
Section: Calcium Hydroxylapatitementioning
confidence: 92%
“…A subsequent splitface study demonstrated comparable aesthetic correction at six months between CaHA and CaHA mixed with lidocaineaine. 14 The elasticity and pH of CaHA are not affected by the addition of lidocaine.…”
Section: Calcium Hydroxylapatite (Caha)mentioning
confidence: 98%